(untitled) (Research, Society and Development, 2022)
Much of the current scientific production aims to investigate the consequences caused by the infection of the virus that causes COVID-19. It is known that this virus has a direct relationship with numerous deaths of pregnant women and, for this reason, it is understood the need to investigate the factors associated with SARS-CoV-2 in pregnancy. The objective of this study is to analyze, from the scientific literature, the consequences associated with COVID-19 in the gestational period. This is an integrative review study, carried out after a bibliometric analysis on the ISI Web of Knowledge/Web of Science™ in the time frame of 2020 and 2021, using the descriptors “Pregnancy” AND “COVID-19” AND “Woman”. The articles were selected and ranked in order of greater relevance by exporting the data to the HistCite™ bibliometric analysis software. The five articles that presented the highest citation rates were selected according to the results provided by the software. The results mainly show changes in psychosocial domains in the gestational period and that SARS-CoV-2 virus infection in more severe clinical cases is associated with existing pathological conditions. It is observed that women in the third trimester of pregnancy are more likely to have clinical worsening by SARS-CoV-2, especially when they present with obesity, hypertension and heart disease. In order for the damage to the health of the woman and the fetus to be negligible, health care in a multidisciplinary context is suggested, considering the importance of integral health in the gestation period and in the face of exposure to the SARS-CoV-2 virus.